2014
DOI: 10.5539/gjhs.v6n3p90
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Trace Elements to Aerobic Maximal Exercise in Elite Sportsmen

Abstract: Trace elements are chemical elements needed in minute quantities for the proper growth, development, and physiology of the organism. In biochemistry, a trace element is also referred to as a micronutrient. Trace elements, such as nickel, cadmium, aluminum, silver, chromium, molybdenum, germanium, tin, titanium, tungsten, scandium, are found naturally in the environment and human exposure derives from a variety of sources, including air, drinking water and food. The Purpose of this study was investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
1
13
1
3
Order By: Relevance
“…The results of studies on animals indicate a potentially beneficial effect of chromium (III), e.g. on the prevention of diabetic microvascular complications in kidneys or on the prevention of atherosclerosis and heart disease, on glycaemic normalization, or as weight loss supplements [5,23,24,25]. However, other data do not support these results [21,26,27].…”
Section: State Of Knowledgementioning
confidence: 99%
“…The results of studies on animals indicate a potentially beneficial effect of chromium (III), e.g. on the prevention of diabetic microvascular complications in kidneys or on the prevention of atherosclerosis and heart disease, on glycaemic normalization, or as weight loss supplements [5,23,24,25]. However, other data do not support these results [21,26,27].…”
Section: State Of Knowledgementioning
confidence: 99%
“…As a matter of fact, the study of Afridi et al [20] showed that the hair of persons suffering from skin diseases possesses greater concentration of chromium than the hair of healthy subjects. Otag et al [26] found greater concentrate of chromium in the blood serum of elite athletes developing aerobic capacity comparing to the results obtained from combat sports athletes. Nevertheless, our research demonstrates statistically greater values (P < 0.012) of chromium in combat sports representatives' hair comparing to the values of athletes practicing endurance sports.…”
Section: Discussionmentioning
confidence: 88%
“…Among numerous publications about the role of necessary for a human macro-and microelements, scientific works dealing with the impact of training load on the concentration of these elements in hair or blood serum are found [24][25][26]. However, the studies dealing with the question of physical load character influence on concentration of macro-and microelements in physically active persons' hair are not enough yet.…”
mentioning
confidence: 99%
“…[1][2][3][4] Currently available novel methods for trace Cr(VI) determination rely on chromium speciation based on ion chromatography, high-performance liquid chromatography or solid phase or liquid-liquid extraction coupled to atomic absorption and emission spectrometry or ICP-MS, [5][6][7][8][9][10][11] To avoid the need for separation of Cr(III) and Cr(VI) selective reagents were proposed, which react selectively with Cr(VI), such as rhodamine B hydrazide for spectrofluorimetric detection, 12 or well known diphenylcarbazide for spectrophotometric determination, which was recently significantly improved in sensitivity by using long-pathlength molecular absorption spectroscopy, or optical waveguide sensors. [13][14][15][16] However, there are several problems of the determination of trace amounts of this metal-production monitoring in environmental analysis, 17 cosmetic industry, 18 rapid clinical diagnostics, 19 several problems of sports medicine 20 -require rapid monitoring or (and) speciation analysis, which cannot be implemented by these techniques. Moreover, solving these problems require developing compact instruments and tests providing the possibilities of rapid and mobile analysis and diagnostics with high sensitivity (at the level of 10-100 nmol L -1 or lower 1,2 but without stationary in-laboratory equipment for example in the case of ICP-AES and ICP-MS.…”
Section: Introductionmentioning
confidence: 99%